1989
DOI: 10.1111/j.1475-1313.1989.tb00913.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial summation in young and elderly observers

Abstract: We measured detection thresholds for targets over a range of sizes at both photopic and scotopic luminance levels in young and elderly observers, and used these data to estimate spatial summation areas 10 degrees in the retinal periphery. There were differences in detection thresholds between the young and old groups at photopic and scotopic luminances, but no differences in spatial summation areas at either background luminance level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 11 publications
(8 reference statements)
2
8
0
Order By: Relevance
“…A majority of research has reported that aging does not alter the summation area [5,19,22,24]. Given that previous research has demonstrated that age has little effect on sensitivity to low spatial frequencies [13,27,51] and sensitivity improves when the target is temporally modulated [30,49] as it was in our case, makes our findings consistent with this literature.…”
Section: Clinical Spatial Summationsupporting
confidence: 93%
“…A majority of research has reported that aging does not alter the summation area [5,19,22,24]. Given that previous research has demonstrated that age has little effect on sensitivity to low spatial frequencies [13,27,51] and sensitivity improves when the target is temporally modulated [30,49] as it was in our case, makes our findings consistent with this literature.…”
Section: Clinical Spatial Summationsupporting
confidence: 93%
“…The average contrast energy values obtained (and 95% confidence intervals) were 17.94 (16.01, 19.94) for the younger observers and 24.34 (21.29, 27.47) for the older observers. As expected from previous investigations (Brown, Peierken, Bowman, & Crassini, 1989; Latham, Whitaker, & Wild, 1994; Werner et al, 2000), photopic increment thresholds are significantly elevated in older observers for foveal stimuli, but there is no significant change in spatial summation area with age.…”
Section: Resultssupporting
confidence: 87%
“…Larger, rather than smaller, summation areas for older compared to younger participants have been reported for static targets under scotopic viewing conditions (e.g., Schefrin et al, 1998). However, the majority of studies that have compared spatial summation for achromatic and chromatic static targets in young and old participants have, in the main, found no age-related differences in Ricco’s area (Dannheim and Drance, 1971; Brown et al, 1989; Redmond et al, 2010). This also appears to be the case for temporally-modulated targets (Zele et al, 2006).…”
Section: Discussionmentioning
confidence: 99%